Fuzzy Control System for Predicting The Quality of Thermally Processed Raw Milk - Büşra UZUN; Novruz ALLAHVERDI (International Journal of Applied Methods in Electronics and Computers, 2021)
Milk, which has a very important place in human nutrition, can be harmful in terms of human health when it is not produced, stored, processed, and necessary controls are performed under hygienic conditions. Even if raw milk contains a small number of bacteria, it is degraded in a very short time after the milking by the effects of microorganisms transmitted from the environment in various ways and constitutes the potential source of many pathogens that cause diseases in humans. Milk proteins contain essential amino acids that cannot be synthesized by the human body and must be taken from the outside. The microorganism load of milk is one of the most important indicators in determining milk quality and determining the hygienic properties of milk in the process from raw milk production to consumption. Fuzzy logic, which is frequently used in the solution of problems that occur in uncertain situations such as quality assessment in recent years, is one of the artificial intelligence methods. In this study, it was aimed to develop a fuzzy logic-based decision support system aimed at predicting the deterioration of heat-treated raw milk. As the subject of this project, it was developed to determine whether the milk produced in troops, farms and cooperatives is spoiled before the milk goes from production households to businesses.